PANDANGAN ALKITAB TENTANG KONFLIK - Gerry C.J. Takaria (Fakultas Filsafat Universitas Advent Indonesia, 2014)
Bible discusses thoroughly about the conflicts that occurred between the fellow children of God in biblical times it was written. Â Nothing is covered up, everything is open to the clearly written by the writers of the Bible with the intent to be learned by all of God's people in every age, when they face the conflict. Is it a sin Conflict? Â This is a question often asked by the people of God, so many of God's people cannot put themselves properly in accordance with the will of God when they are engaged or see a conflict occurred. Â Above questions need to be answered with firmness in accordance with the biblical view. The Bible answers these questions clearly: 1. Conflict is as old as sin, and will continue to exist as long as there is sin in the world; 2. Conflict is not a sin. When we unite our will with God's will, but we will certainly be in conflict with the people who are not doing the will of God while defending the will of God; 3. In a conflict situation God has asked us to make it as an opportunity to serve and show the love of God; 4. The Bible gives us 10 advices very precise that we can use when we are in a conflict situation.